The Role of Jayengrana in the Golek Rod Puppet Show During Javanese Succession War - Septarina, Sri Wahyuning; Artayasa, I Nyoman (International Journal of Culture and Art Studies, 2020)
The second Javanese succession war began after Pakubuwono I and the Company won the first Javanese succession war. Jayengrana struggling together with the descendants of the Sultan of Mataram succeeded in making Pakubuwono I. anxious. The second Javanese succession war illustrated the spirit of the struggle of the son of Untung Surapati in fighting for truth and justice. The two problems discussed in this article are to make objective reconstruction of the past. Second, how the influence of Islam on the kingdoms in Java. The author collects and enforces facts to get a conclusion in a scary show. The study method includes qualitative analysis, the historical approach of Karl Marx, and F. Engels's perspective in understanding history as a past event.